2018
DOI: 10.1111/luts.12229
|View full text |Cite
|
Sign up to set email alerts
|

A Danish population‐based cohort study of desmopressin use in adults with nocturia or nocturnal enuresis

Abstract: This study provides insights into desmopressin use among Danish adults. Nearly half the prescriptions were to patients aged ≥65 years, despite historical manufacturer recommendations that desmopressin be restricted to patients <65 years of age. NE is considered a childhood condition, but desmopressin use for adult NE increased with age. A greater proportion of desmopressin prescriptions to women than men were for the lowest dose, consistent with greater sensitivity to desmopressin in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…2 The use of desmopressin for NE was characterized in a Danish population-based study, which found the rate of use increased from approximately 50/100 000 women in their 50's to 150/100 000 for women in their 90's. 22 While we can perhaps extrapolate a benefit with desmopressin from the nocturia literature 23 or the pediatric literature, 24 we are not aware of any studies on the use of desmopressin for elderly patients with NE. This is concerning due to the potential risk of hyponatremia, which in some cases can be lifethreatening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The use of desmopressin for NE was characterized in a Danish population-based study, which found the rate of use increased from approximately 50/100 000 women in their 50's to 150/100 000 for women in their 90's. 22 While we can perhaps extrapolate a benefit with desmopressin from the nocturia literature 23 or the pediatric literature, 24 we are not aware of any studies on the use of desmopressin for elderly patients with NE. This is concerning due to the potential risk of hyponatremia, which in some cases can be lifethreatening.…”
Section: Resultsmentioning
confidence: 99%
“…Historical studies include the use of aversion therapy and shaming (which are not ethical for use today) and enuresis alarms (which were not found to be very effective in the elderly) 2 . The use of desmopressin for NE was characterized in a Danish population‐based study, which found the rate of use increased from approximately 50/100 000 women in their 50's to 150/100 000 for women in their 90's 22 . While we can perhaps extrapolate a benefit with desmopressin from the nocturia literature 23 or the pediatric literature, 24 we are not aware of any studies on the use of desmopressin for elderly patients with NE.…”
Section: Discussionmentioning
confidence: 99%